Analisis penggunaan gadget mahasiswa baru UIN Maulana Malik Ibrahim Malang 2025 - Hidayah, Muhammad Taufiq (Maliki Interdisciplinary Journal, 2025)
Technological developments in today’s era are developing very rapidly. Therefore, this technological development has a significant impact on new students, especially new students who are still adapting to technology. This analysis aims to analyze the impact of the dependence of new students of UIN Maulana Malik Ibrahim Malang 2025 on gadgets, both in work/learning, entertainment, and communication. Although gadgets also provide numerous benefits in educational development, especially at the student level, there are also many negative impacts in communication or entertainment or even in education. The results of this analysis indicate that quite a few new students of UIN Maulana Malik Ibrahim Malang 2025 are still dependent on gadgets, especially on the negative impacts of gadgets.